EFEITO DA SACAROSE NA MORFOGÊNESE DOS GAMETÓFITOS DE Pecluma ptilodon (KUNZE) PRICE (POLYPODIACEAE) IN VITRO - DE LIMA ROCHA, MARIA AUCILENE; SOARES E SILVA, LUCIA HELENA; DA SILVA FILHO, JOSÉ GETÚLIO; TORRES, ANTONIO CARLOS (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
The development of gamethophyte of Pecluma ptilodon (Kunze) Price was described from in vitro spores germination. Fertile fronds were collected from plants growing in galery forest, in the right margin of the river Couros, in the Portal da Chapada, in Alto Paraíso, GO. The fronds were placed in plastic bags and frictionated for spores release. The spores were disinfested with 0.8% sodium hypochlorite solution, for 20 minutes, inoculated in medium containing macro and micronutrients MS and vitamins, supplemented with sucrose (0.0; 1.0; 2.0; 3.0 and 4.0%). The cultures were maintained in growth chamber with 16-hr daily exposure to 30 mol m-2 s-1 photon flux density illumination from fluorescent lamps. Spores germination occurred from 12 to 15 days after inoculation, showing Vittaria pattern, and the development of the prothallium follow the Aspidium type. The young prothallium is spatulated and ovalated in shape and reached the heart-shaped morphology after 65 day of germination, showing trichomes differentiation and leptosporagiated gametophytes. Gametangia are classified as leptosporangiate ferns type